A novel myeloid cell marker genes related signature can indicate immune infiltration and predict prognosis of hepatocellular carcinoma: Integrated analysis of bulk and single-cell RNA sequencing - Zheng, Su-Su; Wu, Yan-Fang; Zhang, Bo-Heng; Huang, Cheng; Xue, Tong-Chun (Frontiers in Molecular Biosciences, 2023)
Myeloid cells are physiologically related to innate immunity and inflammation. Tumor-associated myeloid cells gained increasing interest because of their critical roles in tumor progression and anticancer immune responses in human malignancies. However, the associations between tumor-associated myeloid cell-related genes and hepatocellular carcinoma have yet to be revealed. Here, through the integrating analysis of bulk and single-cell RNA (scRNA) sequencing of public HCC samples, we developed a gene signature to investigate the role of HCC-specific myeloid signature genes in HCC patients. We firstly defined 317 myeloid cell marker genes through analyzing scRNA data of HCC from the GEO dataset. After selecting the differentially expressed genes, eleven genes were also proved prognostic. Then we built a gene signature from the TCGA cohort and verified further with the ICGC dataset by applying the LASSO Cox method. An eight genes signature (FABP5, C15orf48, PABPC1, TUBA1B, AKR1C3, NQO1, AKR1B10, SPP1) was achieved finally. Patients in the high risk group correlated with higher tumor stages and poor survival than those in the low-risk group. The risk score was proved to be an independent risk factor for prognosis. The high risk group had higher infiltrations of dendritic cells, macrophages and Tregs. And the APC co-inhibition, T cell co-inhibition pathways were also activated. Besides, the risk score positively correlated with multidrug resistance proteins. In conclusion, our myeloid cell marker genes related signature can predict patients’ survival and may also indicate the levels of immune infiltration and drug resistance.